The Knowledge, Attitude and Practice of Nurses, Technicians and Sanitary Workers Regarding Biomedical Waste Management at Healthcare Establishments of Dera Ismail Khan, Pakistan: Biomedical Waste Management among Healthcare Workers - Qadir, Samina; Bano, Raheela; Iqbal, Anil; Saddozai, Muhammad; Gul, Maira; Younis, Muhammad; Dastageer, Fatima; Mussab, Muhammad; Noor, Maheen (Pakistan Journal of Health Sciences, 2024)
Risk waste generated in hospitals can cause some serious health and environment related problems, if not disposed properly. Objective: To assess the knowledge, attitude and practice of healthcare workers regarding Biomedical Waste (BMW) management and to find out any significant difference across different sociodemographic variables. Methods: This was a cross sectional study conducted from 20th February to 20th August 2023. Sampling technique was consecutive non probability with a sample size of 287. Research variables were knowledge, attitude and practice. T-test and One-way ANOVA test were used to show statistically significant difference between research variables across demographic variables at p-value of ≤ 0.05. Results: 287 health care workers participated in this study. Around 84% nurses, 78% technicians and 64% sanitary worker have good knowledge about BMW management. Remaining participants had fair knowledge and none of the health care workers in any category had poor knowledge about BMW. 83% of the total participants from all three categories of workers had a good attitude regarding BMW management whereas around 16.7% participants had a fair attitude while 0.3% had a poor attitude. However, only 1% had good practices while 62% had poor practice and the remaining 37% participants had fair practice. It was found there was a statistically significant association of the category of workers with knowledge. Conclusions: The healthcare workers have good knowledge and attitude regarding BMW disposal but the practice was either fair or poor.